# Simplify 4x^2-36/x^2+2x-15*2x^2+11x+5/16x^2+16x-96/6x^2-7x+2/3x^2-4x-4

Posted by on

• Level 2:

An expert who has achieved level 2 by getting 100 points

MVP:

An expert that got 5 achievements.

Vice President:

An expert whose answer got voted for 100 times.

Sniper:

An expert who has posted more than 50 answers, of which 90% or more were rated as helpful.

• Expert

-42x^2 - 36/x^2 + 18x + 47/48x^2 - 4

I am confident that this is the simplified form.

Posted on Mar 16, 2011

• Level 2:

An expert who has achieved level 2 by getting 100 points

MVP:

An expert that got 5 achievements.

Governor:

An expert whose answer got voted for 20 times.

Hot-Shot:

An expert who has answered 20 questions.

• Expert

-26 x^2-2449/(48 x^2)+18 x-4 or -(1248 x^4-864 x^3+192 x^2+2449)/(48 x^2)

Posted on Mar 17, 2011

Hi,
a 6ya expert can help you resolve that issue over the phone in a minute or two.
Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.
the service is completely free and covers almost anything you can think of.(from cars to computers, handyman, and even drones)
Goodluck!

Posted on Jan 02, 2017

×

my-video-file.mp4

×

## Related Questions:

### Solve: 7(3x+5) = 8x - (1-4x)?

Let's rewrite as

7(3x+5) = 8x -1(1-4x)
Let's distribute
21x + 35 = 8x -1 + 4x
collect like terms
21x + 35 = 12x -1
Put all the x's on one side by subtracting 12x from both sides
21x -12x + 35 = 12x -1 -12x
simplify
9x + 35 = -1
get all the constants on the right side
9x + 35 - 35 = -1 - 35
9x = -36
divide both sides by 9 to get x by itself
9x /9 = -36/9
x = -4

check in original equation

7(3(-4)+5) = 8(-4) -(1-4(-4))
7(-12+5) = -32 - (1+16)
7 (-7) = -32 - (17)
-49 = -32-17
-49 = -49

Jan 04, 2017 | Homework

### Simple equations

That's an expression, not an equation, which simplifies to 7x-5

Mar 05, 2014 | Computers & Internet

### -4x-3(x-1)=17

-4x -3(x-1)=17 -4x-3x+3=17 -7x=17-3 -7x=14 X=-14/7 X= -2

Oct 27, 2011 | SoftMath Algebrator - Algebra Homework...

### 3x(7x+6x)

For 3x(7x+6x)=0, x=0
For 3x(7x+6x)=1, x=1/39
For 3x(7x+6x)=2, x=2/39
For 3x(7x+6x)=3, x=3/39 or 1/13
For 3x(7x+6x)=4, x=4/39
And so on...

Jun 22, 2011 | Acer Aspire One Netbook

### -3x+3+4x+2 simplify

-3x + 3 + 4x +2

2 + 3 = 5, so we simplify that bit:

-3x + 4x + 5

Then we'll look at the 'x' bits.  We're multiplying x by -3 and we're also multiplying by 4.  We don't need all that, so to get the total amount of times we need to multiply x, we add -3 and 4, which gives us 1x...or just x.

So:

Mar 23, 2010 | Wise Solutions Wise Installation System...

### 7x-3+3x=-53 what is the value of 4x+9

7x-3 + 3x = -53
7x + 3x - 3 = -53
10x - 3 = -53
10x = -53 + 3
10x = -50
x = -5
Therefore 4x + 9 is equal to 4 times (-5) plus 9
-20 + 9 equals -11

Dec 17, 2008 | SoftMath Algebrator - Algebra Homework...

### Simplify

[3(x-5)-4(-3x+2)]-[4(6-x)]
[(3x-15)-(12x+8)]-(24-4x)
(-9x-23)-(24-4x)
-13x-(-1)

Sep 13, 2008 | Texas Instruments TI-84 Plus Calculator

### Variables

Hello,
This calculator cannot handle symbolic algebra.
Use the rules to simplify the expressions: Get rid of the parentheses using distributivity od multiplication with respect to addition; group similar terms (terms with x, terms without x).
Hope it helps.

May 07, 2008 | Casio FX-115ES Scientific Calculator

## Open Questions:

#### Related Topics:

127 people viewed this question

Level 3 Expert

Level 3 Expert